Boedal Pailit: Keabsahan Perjanjian Pengikatan Jual Beli Tanah dan Bangunan - Machfudi, Aliyah Samantha; Yulianingsih, Wiwin (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
A Sale and Purchase Agreement is an agreement between the development party or seller and the buyer to carry out land and/or building sale and purchase activities made before a Notary. In its development, the practice of buying and selling which is bound by a Sales and Purchase Agreement (PPJB) often experiences problems. This research will discuss the issue of Binding Sale and Purchase Agreements for bankrupt companies. The method used in this research is normative juridical which is based on statutory regulations, legal theory and expert opinions. The author collected primary and secondary data which was then analyzed qualitatively, namely linking descriptive data to a particular issue which was linked to literature and opinions of legal experts and based on applicable laws and regulations. The results of this research explain the validity of the Sale and Purchase Agreement (PPJB) whose object is entered into bankruptcy and the legal consequences of having a Sale and Purchase Agreement (PPJB) whose object is entered into bankruptcy. From this analysis, it can be concluded that an agreement whose object is entering the bankruptcy court is an invalid agreement because it does not comply with the legal requirements of the agreement. It is hoped that the results of this research can contribute ideas to parties in buying and selling to pay more attention to existing conditions before making a sale and purchase agreement.